2016
DOI: 10.9787/pbb.2016.4.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Related with Defense Responses against Pathogen Infections in Vitis flexuosa

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. Quantitative real-time PCR revealed that R and R-related genes in V. flexuosa induced defense responses through expression of genes in SA-pathway rather than in the JA-pathway, and R-related genes were more clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Research efforts focused on gene expression profiling of V. flexuosa have identified R-related genes, such as VfRLK, VfRPS5-like, and VfCXE, which may contribute to E. ampelina resistance through SA and HR signaling pathways. Expression levels of these genes show a strong correlation with the accumulation of lignin, phytoalexin levels and anthocyanin biosynthesis during E. ampelina infection [18]. Other genes that have been linked to E. ampelina resistance encode chitinase, stilbene synthase, chalcone synthase, polygalacturonase-inhibitor protein, lipid transfer-protein, adenosine triphosphate synthase, glutamine synthetase, and ribulose 1-5 bisphosphate-carboxylase [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research efforts focused on gene expression profiling of V. flexuosa have identified R-related genes, such as VfRLK, VfRPS5-like, and VfCXE, which may contribute to E. ampelina resistance through SA and HR signaling pathways. Expression levels of these genes show a strong correlation with the accumulation of lignin, phytoalexin levels and anthocyanin biosynthesis during E. ampelina infection [18]. Other genes that have been linked to E. ampelina resistance encode chitinase, stilbene synthase, chalcone synthase, polygalacturonase-inhibitor protein, lipid transfer-protein, adenosine triphosphate synthase, glutamine synthetase, and ribulose 1-5 bisphosphate-carboxylase [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis of V. flexuosa infected with E. ampelina highlighted the diversity of genes and pathways regulated by E. ampelina infection [25], while another study reported significant changes in the expression of transcripts associated with SA-and JA-mediated pathways and flavonoid biosynthesis in grapevine following E. ampelina infection [18].…”
Section: Introductionmentioning
confidence: 99%
“…: Elsinoë ampelina) (Murria et al 2018c). Em V. flexuosa, genes relacionados à biossíntese de flavonoides também foram regulados em resposta à infecção por E. ampelina (Islam et al 2016). Segundo os autores, os resultados obtidos no estudo sugerem que os mecanismos de defesa da espécie contra o patógeno incluem a lignificação e produção de fitoalexina e antocianina.…”
Section: ) Eunclassified
“…A concentração de compostos fenólicos totais e a atividade das enzimas peroxidase e polifenoloxidase, por exemplo, foram maiores em cultivares resistentes tanto na forma constitutiva como induzida (Shankar e Jindal 2001;Murria et al 2018a) o que possibilitou relacionálos diretamente à resistência à antracnose. O aumento no teor de flavonoides após a infecção por Elsinoë ampelina correspondeu a outro parâmetro bioquímico relacionado a defesa em Vitis vinifera, comprovado tanto por análises bioquímicas (Rusjan et al 2012) como por expressão gênica (Islam et al 2016). Além disso, análises nos teores de clorofilas vêm sendo realizadas para avaliar o impacto das lesões sobre a atividade fotossintética (Rusjan et al 2012;Murria et al 2018b;.…”
Section: Introductionunclassified